2011
DOI: 10.1098/rspb.2010.2345
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pink salmon biomass and the body condition of short-tailed shearwaters in the Bering Sea: can fish compete with seabirds?

Abstract: Seabirds and large fishes are important top predators in marine ecosystems, but few studies have explored the potential for competition between these groups. This study investigates the relationship between an observed biennial change of pink salmon (Oncorhynchus gorbuscha) biomass in the central Bering Sea (23 times greater in odd-numbered than in even-numbered years) and the body condition and diet of the short-tailed shearwater (Puffinus tenuirostris) that spends the post-breeding season there. Samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In response to the unexpectedly low return of adult Fraser sockeye salmon in 2009 from the 2007 smolt emigration, investigators reported anomalous oceanographic conditions encountered by sockeye salmon during early marine life. Low sockeye survival was associated with unfavorable winds, high river runoff, and pronounced surface stratification that appeared to cause low prey production and reduced growth Thomson et al 2012;McKinnell et al 2014). Other investigators reported disease and toxic algae blooms in the Strait of Georgia as possible factors (Rensel et al 2010;Miller et al 2011).…”
Section: Oceanographic Prey Life History and Predation Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to the unexpectedly low return of adult Fraser sockeye salmon in 2009 from the 2007 smolt emigration, investigators reported anomalous oceanographic conditions encountered by sockeye salmon during early marine life. Low sockeye survival was associated with unfavorable winds, high river runoff, and pronounced surface stratification that appeared to cause low prey production and reduced growth Thomson et al 2012;McKinnell et al 2014). Other investigators reported disease and toxic algae blooms in the Strait of Georgia as possible factors (Rensel et al 2010;Miller et al 2011).…”
Section: Oceanographic Prey Life History and Predation Effectsmentioning
confidence: 99%
“…Seabird diet, body mass, and reproductive success near the Aleutian Islands are reduced in odd-numbered years when pink salmon abundance is exceptionally high (Toge et al 2011;Springer and van Vliet 2014). In Prince William Sound, recovery of Pacific herring (Clupea pallasii) populations during the 20-year period after the Exxon Valdez oil spill may have been inhibited by competition with juvenile hatchery pink salmon for prey (Pearson et al 2012).…”
Section: Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations in the Bering Sea in odd years of lower body mass and liver mass of short-tailed shearwaters (Puffinus tenuirostris), a Southern Hemisphere seabird that spends the austral winter in the SNPO/BS and Chukchi Sea (52), and two to five times higher Hatch date anomaly Tables S2 and S3 for phenology data for all species tested.…”
Section: Seabirds In a Pink Salmon Contextmentioning
confidence: 99%
“…), euphausiids (Thysanoessa spp. ), squids (Gonatidae), myctophids (Myctophidae), and Atka mackerel (Pleurogrammus monopterygius) are at times also important prey of shearwaters and of resident seabirds wintering in the subarctic North Pacific Ocean and nesting in the Aleutian Islands and Bering Sea (52,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66) (67)(68)(69)(70). One of the most conspicuous patterns over the years, and the one that first alerted us to the possibility of a connection between the birds and pink salmon, is the alternating early (even year)-late (odd year) nesting phenology of tufted puffins (Fratercula cirrhata) at Buldir (Fig.…”
Section: Seabirds In a Pink Salmon Contextmentioning
confidence: 99%